2010
DOI: 10.1111/j.1399-5618.2010.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune diseases, bipolar disorder, and non‐affective psychosis

Abstract: Objective-Clinic-based studies of immune function, as well as comorbidity of autoimmune diseases, bipolar disorder, and schizophrenia, suggest a possible autoimmune etiology. Studies of non-affective psychosis and schizophrenia suggest common etiologies. The objective was to determine the degree to which 30 different autoimmune diseases are antecedent risk factors for bipolar disorder, schizophrenia, and non-affective psychosis.Methods-A cohort of 3.57 million births in Denmark was linked to the Psychiatric Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
186
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(199 citation statements)
references
References 44 publications
11
186
1
1
Order By: Relevance
“…A protective effect of CMV was previously reported in patients with multiple sclerosis (Zivadinov et al, 2006;Pirko et al, 2012). Although an autoimmune nature of schizophrenia has not been determined (Schattner et al, 1996;Goldsmith and Rogers, 2008), results of some studies are suggestive of the possibility that autoimmune components play a role in etiopathogenic pathways leading to schizophrenia, at least in some subgroups of subjects (Eaton et al, 2006;Goldsmith and Rogers, 2008;Eaton et al, 2010;Chen et al, 2012). Because CMV has an immunosuppressive effect (Rubin, 1989;Zivadinov et al, 2006;Varani et al, 2009), it might ameliorate the autoimmune damage and consequently decrease the likelihood of developing schizophrenia in vulnerable individuals with autoimmune reactions, which are potentially implicated in the etiopathophysiology of schizophrenia.…”
Section: Discussionmentioning
confidence: 73%
“…A protective effect of CMV was previously reported in patients with multiple sclerosis (Zivadinov et al, 2006;Pirko et al, 2012). Although an autoimmune nature of schizophrenia has not been determined (Schattner et al, 1996;Goldsmith and Rogers, 2008), results of some studies are suggestive of the possibility that autoimmune components play a role in etiopathogenic pathways leading to schizophrenia, at least in some subgroups of subjects (Eaton et al, 2006;Goldsmith and Rogers, 2008;Eaton et al, 2010;Chen et al, 2012). Because CMV has an immunosuppressive effect (Rubin, 1989;Zivadinov et al, 2006;Varani et al, 2009), it might ameliorate the autoimmune damage and consequently decrease the likelihood of developing schizophrenia in vulnerable individuals with autoimmune reactions, which are potentially implicated in the etiopathophysiology of schizophrenia.…”
Section: Discussionmentioning
confidence: 73%
“…Together, these data are consistent with the hypothesis that immunization with M. vaccae can prevent stress-induced exaggeration of colonic inflammation and downstream effects on anxiety-and fear-like behavior. As such, immunization with heat-killed preparations of immunoregulatory bacteria may have utility in prevention of anxiety and affective disorders and their medical comorbidity, including exaggerated autoimmunity (11,59) and exaggerated symptoms of IBD (12,11,59).…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported an association between autoimmune disease and bipolar disorder; including a Danish study that found that Guillain–Barre syndrome, Crohn's disease, and autoimmune hepatitis were associated with an increased risk of bipolar disorder (Eaton et al. 2010). In an American study, elevated anti‐Saccharomyces cerevisiae antibodies, a marker of gastrointestinal inflammation, were associated with an increased risk of bipolar disorder (Severance et al.…”
Section: Discussionmentioning
confidence: 99%